Adenomatoid odontogenic tumor in anterior maxilla: A case report - Gopalakrishnan, V; Charles, NSC; Choube, Amolika (Indian Journal of Case Reports, 2024)
Adenomatoid odontogenic tumor (AOT) is an uncommon benign lesion of odontogenic origin. This tumor mainly affects young individuals in the second decade with a female predilection and is most commonly located in the anterior maxilla, usually associated with an impacted canine tooth. The aim of this report is to discuss the case of a 24-year-old female with AOT in the maxillary incisor region and includes the surgical management of the case.